EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISIONS (STAD) DALAM MENINGKATKAN PENGETAHUAN MATEMATIKA PESERTA DIDIK KELAS V SEKOLAH DASAR - Arinda, Ayu; Sunyono; Miranda Abung; Herpratiwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The problem addressed in this study was the low level of mathematical knowledge among fifth-grade elementary school students. This study aimed to determine the effectiveness of the Student Teams Achievement Division (STAD) cooperative learning model in improving students’ mathematical knowledge. A quasi-experimental design with a nonequivalent control group design was employed. The population consisted of 46 students. Saturated sampling was applied, with 22 students from class V B assigned to the experimental group and 24 students from class V A assigned to the control group. Data were collected using pretests and posttests, as well as through observation. The data were analyzed using the N-gain test. The results indicated that the implementation of the STAD cooperative learning model was effective in improving the mathematical knowledge of fifth-grade students at SD Negeri 3 Metro Pusat.